Nutritional Status and Smoking Habits with The Incidence of Coronary Heart Disease : Status Gizi Dan Kebiasaan Merokok Dengan Kejadian Penyakit Jantung Koroner - Hisyam K, Muhammad; Aisah; Ariyanto (Jurnal Diskursus Ilmiah Kesehatan, 2024)
Background: Based on Riskesdas data for 2018, the incidence of coronary heart disease in Indonesia is 1.5%. It is estimated that 1 in 15 Indonesians suffers from coronary heart disease. Aims: The purpose of this study was to determine the relationship between nutritional status and smoking habits with the incidence of coronary heart disease in patients at the Tanjung Pinang Health Center, Jambi City. Methods: The design used in this research is quantitative research with a cross-sectional approach. This research was conducted at the Tanjung Pinang Health Center, Jambi City in January-August 2023. The population in this study were patients at the Tanjung Pinang Health Center, Jambi City, totaling 428 and a sample of 79 respondents. The sampling technique was purposive sampling. The data analysis used was univariate and bivariate analysis using the Chi-Square statistical test. Result: The results of this study are that there is no relationship between nutritional status and coronary heart disease with a p-value (0.136), and there is a relationship between smoking habits and coronary heart disease with a p-value (0.001). Conclusions:  There is no significant relationship between nutritional status and coronary heart disease, but there is a relationship between smoking habits and coronary heart disease at the Tanjung Pinang Health Center.